Studi Jenis Serbuk Sari yang Terdapat pada Saluran Pernapasan Atas Penderita Ispa di RSUD Dr. Kanujoso Djatiwibowo Balikpapan - Sabila, Nabila Dienna; Syafrizal, Syafrizal; Susanto, Dwi (BIOPROSPEK: Jurnal Ilmiah Biologi, 2016)
This research was conducted in May 2016 in RSUD dr. Kanujoso Djatiwibowo Balikpapan by using acetolysis method. This aims to determine the pollen morphology and determine the plant species that becomes the pollen source which triggers the ARI also determine the periodic calendar of otolaringology patients in RSUD dr. Kanujoso Djatiwibowo Balikpapan all the time. The pollen analysis results on a sample of ARI mucus patients in RSUD dr. Kanujoso Djatiwibowo Balikpapan, was found there are 4 plant species and 3 families. The plants which expected dominating as the pollen source that triggers ARI are from Cyperaceae family which is Scirpus lacustris, Gramineae family which are Oryza sativa and Saccharum spontaneum also Liliaceae family which is Lilium regale. Based on the pollen morphology (shape, size, ornament and aperture), pollens with monad unit dominate the sample. The pollen shape are various from prolate, oblate spheroidal, subprolate and oblate. Ornament type is psilate. Aperture consists of triporate, pantoporate and inaperture. Therefore, it can be stated that the species of pollen source that triggers ARI has pollen morphology which are simpler and small. Based on ARI patient data in RSUD dr. Kanujoso Djatiwibowo Balikpapan from 2013 to 2015 is known periodically appear at the end of the year to early next year and the ARI interference occurs at the beginning of the dry season (April - May).